Hertz Global Holdings : uses of debt and equity - Rosenthal, Jean, (SAGE Business cases., 2021)
In 2019, Hertz CEO Kathyrn Marinello and CFO Jamere Jackson were satisfied that they had succeeded in streamlining the venerable car rental firm's operations. The company appeared to be doing well as the second-largest rental car company with over 10,000 locations. However, the pair weren't satisfied and next turned to considering how to improve Hertz's capital structure. Marinello and Jackson must now decide if Hertz has taken on too much debt and whether the benefits of debt are worth the increased risk of high costs and bankruptcy.